2018
DOI: 10.1016/j.bone.2018.01.019
|View full text |Cite
|
Sign up to set email alerts
|

The effects of estrogen deficiency on cortical bone microporosity and mineralization

Abstract: Recent studies have demonstrated matrix-mineral alterations in bone tissue surrounding osteocytes in estrogen-deficient animals. While cortical bone porosity has been shown to be a contributor to the mechanical properties of bone tissue, little analysis has been done to investigate the effects of estrogen deficiency on bone's microporosities, including the vascular and osteocyte lacunar porosities. In this study we examined alterations in cortical bone microporosity, mineralization, and cancellous bone archite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
34
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 52 publications
4
34
1
Order By: Relevance
“…5 Estrogen deficiency stimulates cortical porosity and therefore forming resorption areas on the trabecular surface. 6,7 It has been recently demonstrated that osteoporosis treatment exploits on improving bone regeneration or inhibiting bone resorption. 8,9 At the cellular level, interaction and communication between the main bone-cell types, the bone-forming osteoblasts and the bone-degrading osteoclasts, organize the smallest functional unit on bone metabolism including osteogenesis which is reduced/ineffective in osteoporotic bone and the important effect of osteoclastogenesis activation.…”
Section: Introductionmentioning
confidence: 99%
“…5 Estrogen deficiency stimulates cortical porosity and therefore forming resorption areas on the trabecular surface. 6,7 It has been recently demonstrated that osteoporosis treatment exploits on improving bone regeneration or inhibiting bone resorption. 8,9 At the cellular level, interaction and communication between the main bone-cell types, the bone-forming osteoblasts and the bone-degrading osteoclasts, organize the smallest functional unit on bone metabolism including osteogenesis which is reduced/ineffective in osteoporotic bone and the important effect of osteoclastogenesis activation.…”
Section: Introductionmentioning
confidence: 99%
“…but no three‐dimensional analysis of vascular pore changes in response to disuse has been previously reported in adult rats. Interestingly, recent work from our group has shown similar vascular canal changes in the proximal tibial metaphysis of skeletally mature rats in response to estrogen deficiency, a condition associated with the development of postmenopausal osteoporosis . An increase in vascular porosity has been shown to diminish interstitial fluid flow in the lacunar‐canalicular system, possibly altering molecular transport and the transduction of mechanical signals to the osteocytes .…”
Section: Discussionmentioning
confidence: 88%
“…Diminished loading has also been shown to induce osteocyte apoptosis that is spatially associated with recruitment of osteoclasts . Recent studies from our lab have demonstrated alterations of both the vascular and osteocyte lacunar porosities in skeletally mature rats that underwent ovariectomy, a model for postmenopausal osteoporosis . In the rat ovariectomy model, we have shown that an increase in vascular porosity reduces interstitial fluid flow due to mechanical loading, potentially altering bone mechanotransduction and negatively affecting the bone formation/resorption balance …”
mentioning
confidence: 73%
See 1 more Smart Citation
“…Several previous researchers examined the effects of ovariectomy (OVX), including causing morphometric and densitometric changes in the tibia bone [16], being overweight [17], and bone becomes porous [18]. Other researchers also have shown that OVX causes an increase in cortical bone blood vessel porosity and decreased bone mineral [19]. All things that arise because of OVX contribute to bone fragility during the process leading to osteoporosis.…”
Section: Introductionmentioning
confidence: 99%